2017
DOI: 10.1007/s00216-017-0558-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pesticides in sewage sludge from an agro-food industry using QuEChERS extraction followed by analysis with liquid chromatography-tandem mass spectrometry

Abstract: An analytical method was developed and validated for the determination of ten pesticides in sewage sludge coming from an agro-food industry. The method was based on the application of Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) extraction for solid sewage sludge and SPE extraction for sludge aqueous phase, followed by liquid chromatography (LC) coupled to hybrid quadrupole/linear ion trap mass spectrometry (QqLIT-MS). The QuEChERS method was reported 14 years ago and nowadays is mainly applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…The most frequently extraction methods applied to soil samples are ultrasound-assisted extraction (USE), pressurized-liquid extraction (PLE) and microwave-assisted extraction (MAE). 8 However, the QuEChERS (acronym of quick, easy, cheap, effective, rugged and safe) method, which was primary developed for the determination of pesticides in crops, 9 has been successfully applied to the extraction of microcontaminants (including pesticides, pharmaceuticals, veterinary drugs among others) in different environmental commodities such as sewage sludge, 10,11 water, soil, sediments, [12][13][14] agricultural fields which were amended with manure or sludge, 15 agricultural soil 16 and vegetables. 4,17 However, in most cases, the scope of the methods is limited and focused on the monitoring of selected groups of compounds, very often in studies conducted under controlled conditions.…”
mentioning
confidence: 99%
“…The most frequently extraction methods applied to soil samples are ultrasound-assisted extraction (USE), pressurized-liquid extraction (PLE) and microwave-assisted extraction (MAE). 8 However, the QuEChERS (acronym of quick, easy, cheap, effective, rugged and safe) method, which was primary developed for the determination of pesticides in crops, 9 has been successfully applied to the extraction of microcontaminants (including pesticides, pharmaceuticals, veterinary drugs among others) in different environmental commodities such as sewage sludge, 10,11 water, soil, sediments, [12][13][14] agricultural fields which were amended with manure or sludge, 15 agricultural soil 16 and vegetables. 4,17 However, in most cases, the scope of the methods is limited and focused on the monitoring of selected groups of compounds, very often in studies conducted under controlled conditions.…”
mentioning
confidence: 99%
“…Nowadays, it is adapted for the preparation of analysis samples for different matrices and the determination of not only pesticides, but also various chemicals [8,9]. Only a few publications, however, discuss the adaptation of the QuEChERS method for the determination of pesticides in agricultural drainage waters [10], food wastewater [11], industrial wastewater [12], and sewage sludge from an agro-food industry [13]. These methods concern determinations of pesticides from different chemical classes but none of these publications mention captan level determination.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it has been adapted for the preparation of samples of different matrices, e.g., meat, milk, honey, oil, soil, and human fluids and to determine not only pesticides, but also various other classes of chemicals, e.g., volatile organic compounds (VOCs), polycyclic aromatic hydrocarbons (PAHs), mycotoxins, pharmaceuticals, veterinary drugs, flame retardants, and forensic samples [8,9]. Only a few publications, however, describe the adaptation of the QuEChERS method for the determination of pesticides in drainage waters [10], wastewater [11,12], or sewage sludge [13].…”
Section: Introductionmentioning
confidence: 99%
“…The QuEChERS extraction (quick, easy, cheap, effective, rugged and safe) has recently been applied to limited studies regarding the determination of pesticides in sludge samples. In particular QuEChERS was applied to sewage sludge generated from agro-food industry [4], in sludge obtained from wastewater treatment plant [5] and in sludge from a pilot plant [6] in all cases followed by LC-MS/MS. Comparison between PLE and QuEChERS showed that the second was superior for samples of sediment, soil and sludge [5].…”
Section: Introductionmentioning
confidence: 99%